First person - Piotr Soczewka (The Company of Biologists, 2019)
First Person is a series of interviews with the first authors of a selection of papers published in Disease Models & Mechanisms (DMM), helping early-career researchers promote themselves alongside their papers. Piotr Soczewka is first author on 'Yeast-model-based study identified myosin- and calcium-dependent calmodulin signalling as a potential target for drug intervention in chorea-acanthocytosis', published in DMM. Piotr is a PhD student in the lab of Prof. Treresa Żołądek at the Polish Academy of Sciences, Warsaw, Poland, investigating the use of yeast to study neurodegenerative diseases.